BASIS: The blood pressure awareness and insight scale. Issue 4 (10th March 2018) - Gerretsen, Philip; Kim, Julia; Shah, Parita; Quilty, Lena; Balakumar, Thushanthi; Caravaggio, Fernando; Plitman, Eric; Chung, Jun Ku; Iwata, Yusuke; Pollock, Bruce G.; Dash, Satya; Sockalingam, Sanjeev; et al.
Abstract : Impaired illness awareness or not accepting that one has hypertension (HTN) may be an important predictor of treatment adherence and optimal blood pressure control. The purpose of this study was to perform a systematic review of available instruments to evaluate HTN awareness, and subsequently present a novel scale that measures the core domains of subjective illness awareness in HTN. Based on the absence of any validated HTN specific measure identified through our review, the Blood Pressure Awareness and Insight Scale (BASIS) was developed (www.illnessawarenessscales.com ). An online survey platform was used to collect data on 100 participants. BASIS showed good concurrent ( r (98) = .65, P < 0.001) and discriminant validity, internal consistency (Cronbach's α = .75), and 1‐month test‐retest reliability (ICC = 0.77). BASIS is a comprehensive, easy‐to‐use instrument specifically designed to measure subjective HTN awareness. BASIS may be used in research studies and clinical practice to assess the impact of HTN awareness on treatment adherence and clinical outcomes.